The effects of betamethasone on clinical outcome of the late preterm neonates born between 34 and 36 weeks of gestation - Yas Arimi (BMC, 2021)
Abstract Background Prenatal corticosteroid administration in preterm labor is one of the most important treatments available to improve neonatal outcomes; however, its beneficial effects on late preterm infants (after the 34th week of gestation) remained unknown. We aimed to assess the effects of betamethasone on the clinical condition of the late preterm infants born between 34 and 36 weeks of gestation. Methods This retrospective cohort study was performed on 100 consecutive infants born between 34 and 36 weeks of gestation and received betamethasone before delivery as the cases and 100 neonates with the same delivery conditions but without receiving betamethasone. All neonates were followed up within hospitalization to assess the neonatal outcome. Results The neonates receiving betamethasone suffered more from respiratory distress syndrome (49% versus 31%, p = 0.008, RR = 1.59 95% CI (1.12–2.27)) and requiring more respiratory support (71% versus 50%, p = 0.002, RR = 1.43 95% CI (1.13–1.80)) as compared to the control group. There was no difference between the two groups in other neonatal adverse events or death. Conclusion the use of betamethasone in the late preterm period (after 34 weeks of gestation) has no beneficial effects on lung maturity or preventing neonatal adverse outcomes, even may lead to increase the risk for RDS and requiring respiratory support.